Strengthening Islamic literacy as an effort to shape the character of the children of Umeak Baco Rejang Lebong - Aflisia, Noza; Harmi, Hendra; Nurjannah, N. (Universitas Muhammadiyah Malang, 2021)
Islamic literacy plays a role in the formation of Islamic character in the younger generation. By reading a lot and learning about Islam, he will understand the purpose he was created in the world. So that knows how should behave on God's earth. But nowadays many ignore Islamic literacy, so the islamic basis has become very superficial and encourages inappropriate deeds. The purpose of this devotion is to build the character of Islam in children through various literacy activities and help children with financial limitations to get additional quality learning at no cost so as to build them into a smart young generation of Islam. Learning takes place with lecture methods, live methods, Q&A, random game of letters, random words, card games, singing. Forms of activity are reading books, learning Islam and Arabic. The material provided is Islamic morality and Arabic vocabulary. Gradually from week to week children's ability to recite and memorize Arabic is increasing. So are the children's morals that are better than before. Changes in children's behavior are seen to change from loving the environment, appreciating friends, and respecting older people.